Factors Contributing to Undergraduates’ Motivation to Learn the English Language at Selected Universities in Cambodia - Sochea Saroeun; Dina Pen; Sokmuoy Samoun (MASI Mandiri Edukasi, 2025)
This study explores the factors influencing undergraduate students’ motivation to learn English at three selected Cambodian universities: the National University of Cheasim Kamchaymear (NUCK), Svay Rieng University (SRU), and the University of Heng Samrin Thboung Khmum (UHST). The objective was to assess the levels of intrinsic and extrinsic motivation among students and examine their attitudes toward English learning. A quantitative research design was employed using a structured questionnaire, and data were collected from 101 undergraduates through convenience sampling. Results reveal that intrinsic motivation—such as personal interest, enjoyment, and curiosity—strongly correlates with students’ engagement in English learning. Extrinsic factors, including career aspirations and social expectations, also play a significant role, though to a slightly lesser extent. Additionally, while most students perceive English as essential for communication and future success, confidence in speaking varies across participants. This aligns with studies highlighting how social support and willingness to communicate impact learners’ confidence and participation in the language learning environment. The findings provide practical insights for educators and policymakers to design more targeted interventions that support both motivational dimensions, ultimately enhancing English language education in Cambodia.